The Linkage Among Sea Transport, Trade Liberalization and Industrial Development in the Context of CO2: An Empirical Investigation From China - Kalaycı, Salih; Özden, Cihan (Frontiers in Environmental Science, 2021)
The major goal of this paper is to focus on the existing literature regarding the linkage between maritime, trade liberalization and industrial development in the context of CO2 by using econometrical model. In this context, it is attempted to reveal the effects of independent variables on CO2 (dependent variable) for China from 1970 to 2019 (annual data) by implementing Phillips-Perron (PP), Zivot-Andrews unit root tests, FMOLS, DOLS, CCR, ARDL and GMM methods. According to results of FMOLS, DOLS and CCR models there is a long-term stable relationship between sea transportation, trade liberalization, industrial development and carbon dioxide emissions which is proved empirically. Similarly, Short term ARDL estimation results reveal that the main determinants of CO2 in the short-run are changed in industrial development and maritime transport at 1% significance level. Table 6 summarizes the short-term ARDL results and the findings regarding the error correction model. According to Table 6, error correction model works in order to reach short-run adjustment. In the short term, approximately 82% of shocks in industrial development, maritime transport and trade liberalization are compensated within a period of time and the system is re-established in the long term. China produced half of the 1.2 million electric media used worldwide; the government directs its attention to the rehabilitation and reuse of all these lithium-ion batteries. Large-scale production of biofuels can still be several years away. Crude oil might be very difficult to promote alternative fuels on a national scale unless crude oil prices surge so high as to become unaffordable. Authorities underline: China will become the world's number one economy. Now renewable energy will be more important, which should be encouraged to use by government on transportation so as to reduce the CO2 emissions. However, China can be leader excess oil use for transport if they want to dominate the economy worldwide.